Prevalence and risk factors of obesity among senior high school students in the Adansi North District in Ashanti Region of Ghana. - Amoh, Isaac (2017)
A thesis submitted to the Department of Health Promotion and Education, College of Health Sciences, School of Public Health, in partial fulfilment of the requirements for the degree of Master of Public Health in Health Education and Promotion,